Safety Issues With the Use of Antimicrobials in Current Clinical Practice - Kuzmina A.V.; Polivanov V.A.; Asetskaya I.L.; Zyryanov S.K. (Клиническая микробиология и антимикробная химиотерапия, 2015)
Due to increased use of antibiotics in current clinical practice it is very important to evaluate all risks of antimicrobial therapy. Pharmacovigilance plays a vital role in ensuring that doctors, together with the patient, have enough information about safety profile of a drug for treatment. This paper presents some of the results from postmarketing studies of antimicrobial drugs. It shows Russian and international data of frequency and severity of adverse drug reactions to antibiotics in different patient groups, including children and older persons. Practical recommendations for safer use of antimicrobial therapy are proposed in this paper. The authors also discuss topical problems of inappropriate use of antibiotics and antibiotic resistance.